# The center of a circle represented by the equation (x - 5)^{2} + (y + 6)^{2} = 4^{2} is

**Solution:**

The center radius form of the equation of a circle is

(x - h)^{2} + (y - k)^{2} = r^{2}

Where (h, k) is the center

r is the radius

From the question we have

(x - 5)^{2} + (y + 6)^{2} = 4^{2}

Where (5, -6) is the center and 4 is the radius

Therefore, the center of a circle is (5, -6).

## The center of a circle represented by the equation (x - 5)^{2} + (y + 6)^{2} = 4^{2} is

**Summary:**

The center of a circle represented by the equation (x - 5)^{2} + (y + 6)^{2} = 4^{2} is (5, -6).

Math worksheets and

visual curriculum

visual curriculum